Efficacy and safety of everolimus plus exemestane in postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative locally advanced or metastatic breast cancer: Results of the single-arm, phase IIIB 4EVER trial - Tesch, Hans; Marmé, Frederik; Schneeweiss, Andreas (International journal of cancer, 2019)
In BOLERO-2, adding everolimus to exemestane resulted in a twofold increase in median progression-free survival (PFS) vs exemestane in postmenopausal women with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) advanced breast cancer (aBC) after progression on a non-steroidal aromatase inhibitor (NSAI). Here, we report on the open-label, single-arm, phase IIIB 4EVER trial (NCT01626222). This trial evaluated the clinical effectiveness of everolimus plus exemestane in postmenopausal women with HR+, HER2− aBC who had progressed on or after an NSAI, but with no restrictions on the time of progression after NSAI, prior chemotherapy for advanced disease or previous exemestane. The primary endpoint was overall response rate (ORR; i.e. the percentage of patients with a best overall response of complete or partial response per RECIST 1.1) within the first 24 weeks of treatment. Secondary endpoints included PFS, overall survival, safety and health-related quality of life. Between June 2012 and November 2013, 299 patients were enrolled at 82 German centers: 281 patients were evaluable for efficacy and 299 for safety. The ORR was 8.9% (95% confidence interval [CI]: 5.8-12.9%). Median PFS was 5.6 months (95% CI: 5.4-6.0 months). The most frequent grade 3/4 adverse events were stomatitis (8.4%), general physical health deterioration (6.7%), dyspnea (4.7%) and anemia (4.3%). The ORR in 4EVER was lower than in BOLERO-2, likely due to inclusion of patients with more advanced disease and extensive pretreatment. These data confirm the clinical benefits and known safety profile of everolimus plus exemestane in postmenopausal women with HR+, HER2− aBC.
Online 11 Jul 2018
Gesehen am 19.02.2019